Digital Technology Driving Sustainable Development in Rural Ecotourism - Ji, Xiaoxue; Deng, Bin (Economics & Management Review, 2025)
This study investigates the role of digital technologies in advancing sustainable development within rural ecotourism, focusing on integrating e-commerce, e-payment systems, and Internet marketing. While digitalization in tourism is widely discussed, its specific implications for rural ecotourism remain underexplored. This research addresses that gap by adopting a novel theoretical approach that integrates the Triple Bottom Line (TBL), Technology Acceptance Model (TAM), and Destination Management Organization (DMO) frameworks. A cross-sectional survey of 401 stakeholders—tourists, local business owners, community members, and government officials—provides empirical insights into technology adoption, perceived benefits, and implementation challenges. The findings reveal moderately positive perceptions of digital tools across stakeholder groups, with significant concerns about privacy, digital literacy, and connectivity in rural areas. Statistical analysis through descriptive statistics, Analysis of variance (ANOVA), and t-tests shows variation in perceptions by gender but limited differences across age, education, or occupation. The study contributes a new understanding of how digital platforms can enhance economic viability, environmental responsibility, and community participation in rural tourism. This research offers actionable recommendations for stakeholders aiming to implement inclusive, sustainable digital strategies. It advances the academic conversation by linking technology acceptance with sustainable tourism outcomes in rural settings, presenting a practical and theoretical framework for future digital transformation efforts in ecotourism.